Social Media Addiction and Sleep Disturbances Affect the Occurrence of Pre-Menstrual Syndrome - Achyar, Khamidah; Firnandani, Sherly (Alma Ata University Press, 2025)
Background: Pre-Menstrual Syndrome (PMS) is a common condition among adolescent females that can negatively affect daily activities, emotions, and overall quality of life. According to PKRR data from 2020, approximately 90% of women of reproductive age experience PMS, with 80% being adolescents reporting significant disruption in daily life. One contributing factor is sleep disturbance, often associated with hormonal fluctuations prior to menstruation. Additionally, excessive social media use has been shown to influence sleep patterns and mental health, potentially worsening PMS symptoms. This issue is particularly relevant among female university students, who are frequently exposed to social media and academic stress, both of which may impact sleep quality and emotional regulation. Objectives: This study aims to analyze the relationship between social media addiction and sleep disturbances with the incidence of PMS among female students at the Faculty of Health Sciences, Universitas Muhammadiyah Purwokerto.Methods: This study used an observational analytic design with a cross-sectional approach. A total of 92 female students were selected using proportionate stratified random sampling. Research instruments included the Bergen Social Media Addiction Scale (BSMAS), the Pittsburgh Sleep Quality Index (PSQI), and the Shortened Premenstrual Assessment Form (SPAF). Data were analyzed using the Spearman rank correlation test.Results: The findings revealed significant associations between social media addiction and PMS (p = 0.002), as well as between sleep disturbances and PMS (p < 0.001).Conclusions: Social media addiction and sleep disturbances are significantly related to the incidence of PMS among female university students.